Supremeo Popcorn / Nurul Natasya Rosli - Rosli, Nurul Natasya (2021)
Supremeo Popcorn that also known as S.Popcorn is a popcorn that are made by using air-popped which make it as a healthy snack due to low fat and low calories. Our popcorn using just real ingredients for real flavour and we avoid from using artificial flavourings, colourings, and additives. The mission of S.Popcorn is to unite people through a common love for wholesome snacks and new flavours. We hope our snacks will be enjoyed by all people. Meanwhile, our vision is we aim to revolutionise the snack industry. We offer a range of fully coated, round popcorn made from mushroom popcorn kernels. Each product is HALAL, GMP, HACCP certified and our range of flavours are developed according to the latest trend in flavours and snacks. There are three main flavours- Caramel Butter, Salted Egg, and Dark Chocolate with more on the way. Our popcorn is certified according to local and international standards of quality. Even though there are many competitors out there, we are confident with our popcorn because we use 100% real ingredients and no artificial flavouring. We also make sure each bottle and pack are carefully sealed to ensure freshness and a delightful crunch in every bite. Our popcorn is also flavourful because each kernel is fully coated for a mouth-watering taste bud tempting experience. Besides that, our popcorn can be refrigerated and chilled for a different experience. Our popcorn product is available online through many platforms such as Shopee, Lazada and many more. More than just a movie snack our popcorn is the perfect threat to all people who want to take is as picnic snacks, trail mix or as an easy fix for late-night munchies. We have a range of packs for sharing and individual snacking including our foil packs, canister packs and tub packs.